The Role of Profit and Loss Sharing (PLS) in Establishing Economic Stability - Burhansyah, Luki; Janwari, Yadi; Hasanuddin, Muhammad (CV. Strata Persada Academia, 2025)
This study aims to analyze the role of profit and loss sharing (PLS) as a monetary instrument in supporting financial and macroeconomic stability within the framework of the Islamic economic system. Unlike conventional approaches that rely on interest rates, PLS offers a financing alternative based on the principles of justice, partnership, and risk-sharing. Employing a qualitative method through library research, this study examines classical and contemporary literature on Islamic monetary systems using a multidisciplinary approach, including theological, Islamic legal (fiqh al-muamalat), and macroeconomic perspectives. The findings reveal that PLS can enhance resource allocation efficiency, reduce speculative practices, and strengthen the link between the financial and real sectors. Furthermore, PLS contributes to financial inclusion and the growth of productive sectors, particularly micro, small, and medium-sized enterprises (MSMEs), thereby promoting more resilient and sustainable economic stability. Optimizing the role of PLS in Islamic monetary policy requires adaptive regulatory support, increased institutional capacity of Islamic financial institutions, and the development of innovative PLS-based financial products. These findings are expected to contribute to the advancement of Islamic economic theory and offer policy recommendations to foster an inclusive and equitable path toward economic stability.